Comparison of multi criteria decision making (MCDM) methods with respect to performance of food firms listed in BIST - Erdoğan, Namık Kemal; Altınırmak, Serpil; Karamaşa, Çağlar (Copernican Journal of Finance & Accounting, 2016)
Analyzing firms’ performance appropriately is core topic for decision makers working in financial sector under the conditions of imprecise and incomplete information. Purpose of this study is to assess firms’ performance by taking financial ratios and financial experts’ into the account. Therefore firstly weights of criteria and sub criteria related to financial ratios are obtained by using one of the fuzzy ranking methods namely Buckley’s Column Geometric Mean Method. Following to this firms’ final rankings are determined by means of TOPSIS, VIKOR and ELECTRE methods. Also ranking performance of these three methods is interpreted. According to this purpose financial ratios of twenty one food firms listed in BIST for four years period (2011–2014) are acquired and analyzed via these methods.